Systematic Review of Ischemic Post-Stroke Rehabilitation and Its Impact on Motoric Function, Independence and Quality of Life - Nur Fadlilah; Rohematus Soleha; Faisal Hizbuallah; Arvino Aprilian; Eppy Setiyowati (CV. Global Health Science Group, 2025)
According to the World Health Organization (WHO), stroke remains the foremost cause of disability globally and ranks as the second leading cause of mortality. The progression of disability post-stroke is influenced by multiple interrelated factors, including advanced age, pre-existing comorbidities, cognitive dysfunction, and the initial severity of stroke at the time of onset. Various therapeutic approaches, including physical therapy to enhance muscle strength and coordination, occupational therapy to develop skills for performing daily activities, and psychosocial support, are essential components of rehabilitation programs aimed at improving the quality of life for stroke patients Objective this research for analyze the effectiveness of mindfulness therapy as part of ischemic post- stroke rehabilitation strategies in improving patients' quality of life and independence. Methods this research is A systematic review was conducted on studies published between 2020 and 2024. The search terms included: